PENGARUH SUHU LINGKUNGAN TROPIS TERHADAP PENENTUAN JENIS KELAMIN DROSOPHILA - G. Wayan Seregeg (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Based on many research studies conducted it can be concluded that there are more than 250 theories of sex-determination. This means that there is not any single theory on sex-determination. This study aims at uncovering effects of the temperature of the tropical environment on sex-determination in Drosophila. The method undertaken was to collect and count the ratio of males to females, Drosophila directly caught in natural environment. The catching was conducted in three periods, ie.: April 2001, April 2002, and April 2004.The results were as follows: (1) The number of females caught at each periode was much more than males. The ratio of males to females was 1:2; (2) The ratios of males to females at three successive periodes were significantly different at p ≥ 5. The ratios vary due to the influence of several factor, outside the temperature of the environment, on the ratios of males to females in Drosophila.